Effect of social comparison on envy: A predictive study considering psychological and demographic variables among social media users - Khatatbeh, Yahya; Bani Yassin, Omar Saleh; Freihat, Aiman Mohammad (Research Journal in Advanced Humanities, 2025)
Background: Social comparison affects envy in both types and forms of envy, depending on several psychological and social variables, and social media highlight this in general. This study aimed to analyse the influential relationship between social comparison and two types of envy (benign and malignant) among social media users, while testing the interactive role of both age and income in modifying this relationship.Methods: A total of 282 participants of various ages and income groups participated in the study. The Benign and Malicious Envy Scale and Social Comparison Scale were used to assess individuals’ tendencies toward different forms of envy and their patterns of social comparison in order to explore their interrelationship and psychological implications.Results: The results showed that social comparison is one of the most prominent predictive variables for the types of envy among users of social networking sites. Regarding the dimensions of social comparison, opinions were most influential in contributing to envy, while the dimension of performance had a statistically significant negative effect. Interactive analyses showed that the effect of social comparison was affected by age and income variables, wherein 20–24-year-olds) were more affected by both types of envy, while the highest levels of malicious envy were within those who made 5,000–7,000 riyals. These results suggest that social comparison not only directly affects feelings of envy but is also enhanced by its interaction with demographic characteristics. Conclusion: The study recommends designing psychocognitive intervention programs for young people, focusing on developing awareness of health comparison methods and regulating emotions, as well as encouraging the positive and controlled use of social networking sites, especially among the most sensitive groups, to psychological vulnerability.